Redefining the role of syndecans in C. elegans biology. Issue 1 (2nd January 2016) - Gopal, Sandeep; Couchman, John; Pocock, Roger
ABSTRACT: Cytosolic calcium is an important factor during fertilization, development and differentiation. Hence, the control of cytosolic calcium levels has been studied extensively for several decades. Numerous calcium channels have been identified and their mechanism of action elucidated. However, the mode of calcium channel regulation remains elusive. Here we discuss our recent findings regarding the role of syndecans in the regulation of cytosolic calcium levels. Syndecans are transmembrane proteoglycans present in both vertebrates and invertebrates that interact with extracellular ligands resulting in the activation of several downstream signaling pathways. We identified a previously unappreciated role of syndecans in cytosolic calcium regulation in mammals that is conserved in C. elegans . We concluded that calcium regulation is the basic, evolutionarily conserved role for syndecans, which enables them to be integral for multiple cellular functions.